2017
DOI: 10.1111/sji.12596
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Soluble Programmed Death Ligand 1 Expression in Cancers: A Systematic Review and Meta‐analysis

Abstract: The differential expression of soluble programmed death ligand 1 (sPD-L1) has been found in some cancers; however, the correlation between sPD-L1 expression and prognosis value in tumour is still unclear. Here, we conducted a metaanalysis and systematic review to assess the prognostic value of sPD-L1 in patients with cancer. Eligible studies were searched for in the databases including PubMed, Web of Science, ScienceDirect and Wiley Online Library database. The pooled hazard ratios (HRs) with a 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…Since an association between sPD-L1 and prognosis was demonstrated in patients with renal cell carcinoma, the prognostic implications of sPD-L1 have been suggested in several solid cancers and hematologic malignancies [25][26][27][28][29]. A meta-analysis evaluating eight studies and 1102 patients with cancers of the lung, stomach, liver, and biliary tract; lymphoma; and myeloma indicated that a higher level of sPD-L1 was associated with worse OS (HR = 1.60, 95% CI: 1.21-1.99) [30]. However, the clinical relevance of sPD-L1 in patients with PCNSL has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since an association between sPD-L1 and prognosis was demonstrated in patients with renal cell carcinoma, the prognostic implications of sPD-L1 have been suggested in several solid cancers and hematologic malignancies [25][26][27][28][29]. A meta-analysis evaluating eight studies and 1102 patients with cancers of the lung, stomach, liver, and biliary tract; lymphoma; and myeloma indicated that a higher level of sPD-L1 was associated with worse OS (HR = 1.60, 95% CI: 1.21-1.99) [30]. However, the clinical relevance of sPD-L1 in patients with PCNSL has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sPD-L1, which is released from PD-L1-positive cells and binds to the PD-1 receptor, contributes to immunoregulation and can be considered a good surrogate of activation of this pathway. Moreover, sPD-L1 seems to play a role in promoting cancer cells, as was recently reported in a metaanalysis on this topic, in which it emerged as a biomarker of an unfavorable prognosis in patients with cancer 12 . Therefore, in what is likely a multistep process or a concurrent action, these mechanisms -cancer cell mutations and loss of heterozygosity on the one hand and PD-1 pathway activation on the other -participate in the complex relationship between cancer and the immune system, here represented by DM, an autoimmune disease.…”
mentioning
confidence: 55%
“…Since an association between sPD-L1 and prognosis was demonstrated in patients with renal cell carcinoma, the prognostic implications of sPD-L1 have been suggested in several solid cancers and hematologic malignancies [25][26][27][28][29]. A meta-analysis evaluating eight studies and 1,102 patients with cancers of the lung, stomach, liver, and biliary tract; lymphoma; and myeloma indicated that a higher level of sPD-L1 was associated with worse OS (HR = 1.60, 95% CI: 1.21-1.99) [30]. However, the clinical relevance of sPD-L1 in patients with PCNSL has never been reported.…”
Section: Discussionmentioning
confidence: 99%